PEMBUATAN KERAMIK KORDIERIT DENGAN METODE SOL-GEL DAN KARAKTERISASI-NYA - Silvester Tursiloadi (Jurnal Kimia Terapan Indonesia, 2000)
Sol-gel method and melt-quenching as a reference methodwere studied for preparing a-cordierite phase. The solution ofcordierite precursor was prepared from a mixture of Si(O-Et),Al(O-Bu'), and Mg (O-EI)2 in 2-methoxyelhanol. The alkoxidesolution thus obtained was hydrolyzed with NH4OH-water. Thegel obtained was aged 80'C. After aging for more than one day,the products were dried at 120'C for 24 hours in dry oven. Allthe gel powders obtained were heat-treated up to 1050°C. Theirphase transformation was studied by using a DTA and X-raydiffraction. It was found that different crystallization behaviorswere shown by the Al/Si ratio in gel powders. As the amount of.41 atoms decreased the exothermic peak of DTA due tocrystallization shifted to lower temperature and the initialtram/ormation of a-cordierite phase front u-cordierite took placeby heat-treating at 900'C for 1 hour. However, the completetram/ormation of single a-cordierite phase took place at highertemperature than Al-rich samples. Although the calcination wasdone at 1050·C for 1 hr, the phase of u-cor dierite was stillobserved. Transformation of u-cordierite to a-cordierite phasefor Al-rich samples showed al a higher temperature comparedfor Al-poor samples, although the complete transformation tookplace at a relatively low temperature, compared with solid statereaction.The increase in Al concentration will increase the density ofsamples. The density of all samples were increased up to thecalcination temperature of 950·C, and the highest density wasobtained at 1050·C. The sample which was prepared by 'meltquenching'method, showed that the density of the sample was almostthe same although the calcination temperature was increased up tomore than 900'C. After calcination at 1050'C, the Al-rich samplehas a density of around 3,32 g/cm3 (93% of density standardcordierite).